Service marketing strategies for small and medium enterprises : emerging research and opportunities - Rahman, Muhammad Sabbir, 1981-; Zaman, Mahmud Habib, 1981-,eauthor; Hossain, Md. Afnan, 1987- (Hershey, PA : IGI Global, Business Science Reference, 2019)
'This book addresses the growing importance of services and in recognition of unique challenges faced by small and medium enterprises service marketing managers to gain insights and a level playing field thereby attaining sustainability. It also focuses on the knowledge required to implement service strategies to gain competitive advantages'--
Keywords: Small business -- Customer services; Small business marketing; Customer services -- Marketing